Oracle Cloud infrastructure for solutions architects : effectively design enterprise-grade solutions with OCI services - Sarkar, Prasenjit; Ruiz, Guillermo (Packt Publishing, 2021)
Develop enterprise architect skills by building secure, highly available, and cost-effective solutions with Oracle Functions, Terraform, and the Oracle Cloud VMware Solution Key Features Explore Oracle's Gen 2.0 Cloud infrastructure and its high-performance computing capabilities Understand hybrid cloud capabilities and learn to migrate apps from on-premises VMware clusters to OCI Learn to create Kubernetes clusters and run containerized applications on Oracle's Container Engine Book Description Oracle Cloud Infrastructure (OCI) is a set of complementary cloud services that enables you to build and run a wide range of applications and services in a highly available hosted environment. This book is a fast-paced practical guide that will help you develop the capabilities to leverage OCI services and effectively manage your cloud infrastructure. Oracle Cloud Infrastructure for Solutions Architects begins by helping you get to grips with the fundamentals of Oracle Cloud Infrastructure, and moves on to cover the building blocks of the layers of Infrastructure as a Service (IaaS), such as Identity and Access Management (IAM), compute, storage, network, and database. As you advance, you'll delve into the development aspects of OCI, where you'll learn to build cloud-native applications and perform operations on OCI resources as well as use the CLI, API, and SDK. Finally, you'll explore the capabilities of building an Oracle hybrid cloud infrastructure. By the end of this book, you'll have learned how to leverage the OCI and gained a solid understanding of the persona of an architect as well as a developer's perspective. What you will learn Become well-versed with the building blocks of OCI Gen 2.0 Cloud Control access to your cloud resources using IAM components Manage and operate various compute instances Tune and configure various storage options for your apps Develop applications on OCI using OCI Registry (OCIR), Cloud Shell, OCI Container Engine for Kubernetes (OKE), and Service Mesh Discover ways to use object-relational mapping (ORM) to create infrastructure blocks using Terraform code Who this book is for This book is for cloud architects, cloud developers, and DevSecOps engineers who want to learn how to architect and develop on Oracle Cloud Infrastructure by leveraging a wide range of OCI IAAS capabilities. Working knowledge of Linux, exposure to basic programming, and a basic understanding of networking concepts are needed to get the most out of this book.